2014
DOI: 10.1002/cmdc.201400068
|View full text |Cite
|
Sign up to set email alerts
|

Getting to the Source: Selective Drug Targeting of Cancer Stem Cells

Abstract: Cancers are among the most important and most difficult to treat diseases of the 21st century. Conventional therapies include surgery, immunotherapy, and radiotherapy, as well many forms of drug treatments such as tamoxifen and Gleevec. However, these forms of treatment often do not eradicate the cancer stem cells, only managing to decrease the size of the tumor, allowing the cancer to return. The cancer stem cell hypothesis stipulates that malignancy is maintained through self-renewal of cancer stem cells (CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 108 publications
(127 reference statements)
0
10
0
Order By: Relevance
“…In this study, cellular and molecular pharmacological data demonstrate that DLC-carborane compounds target cancer and primary GBM CSCs highly selectively and also that these agents exert a very significant pharmacological behavior while sparing normal cells. Based on the principle of the elimination of CSCs toward achieving patient long-term cure rates in the clinical setting [3,6,7], it is of significance that DLCcarborane compounds exert such remarkable effect on GBM CSC lines. The effect is most meaningfully demonstrated by the determined IC 50 values, which are markedly 18 lower than those calculated for normal cells (ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, cellular and molecular pharmacological data demonstrate that DLC-carborane compounds target cancer and primary GBM CSCs highly selectively and also that these agents exert a very significant pharmacological behavior while sparing normal cells. Based on the principle of the elimination of CSCs toward achieving patient long-term cure rates in the clinical setting [3,6,7], it is of significance that DLCcarborane compounds exert such remarkable effect on GBM CSC lines. The effect is most meaningfully demonstrated by the determined IC 50 values, which are markedly 18 lower than those calculated for normal cells (ca.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that as long as technological advancements empower the translational medicine capacity in enabling the pharmacological exploitation of cancer cell molecular and genomic knowledge, the advances to therapeutically overcome heterogeneity and to target the tumor cell microenvironment will occur at increasing rates [2][3][4][5][6][7][8][9][10]. A major milestone towards organelle-specific drug delivery was reached by the discovery of delocalized lipophilic cations (DLCs) [11].…”
Section: Introductionmentioning
confidence: 99%
“…These methods have been used to design and optimise green pesticides [16][17][18][19][20] in collaboration with Du Pont and Schering Plough, have discovered new peptides and small molecules to control stem cells and cancers, [21][22][23][24][25][26][27] are accelerating the development of biomaterials for implantation and stem cell culture, [28][29][30][31][32][33] have provided new scientific insight into the potential adverse properties of nanomaterials, [34][35][36][37][38] have yielded clinical candidates for Australian SMEs and international companies, and were instrumental in the discovery of antibiotics [39,40] with a novel mode of action for the biotechnology spin off company, Betabiotics. Some of this research is discussed in more detail in the following sections.…”
Section: The Threat and Promise Of The Vastness Of Chemical Spacementioning
confidence: 99%
“…[73,74] Design of small molecules to reprogram somatic and stem cells, and to selectively kill cancer stem cells. [21] Clearly science and technology have moved on very rapidly since Adrien Albert's day, but he would be very pleased to see his area of selective toxicity flourishing in the twenty-first century. …”
Section: Where To Next?mentioning
confidence: 99%
“…It is clear that, while markers such as folate receptors [ 1 ] and other proteins on cancer cells, [ 2 ] or aldehyde dehydrogenase receptors on cancer stem cells [ 3 ] can provide some selective targeting of therapeutics or diagnostics, a single protein marker will not be enough to achieve the selectivity required. A better understanding of the types surface marker populations in specifi c types of cells is necessary to generate the selectivity required to generate maximum effi cacy against cancers, and to avoid effects on healthy bystander cells that also express a subset of these markers.…”
Section: Introductionmentioning
confidence: 99%